The salvation of Israel Jews in Christian eschatology from Paul to the Puritans - Cohen, Jeremy 1953- (Cornell University Press, 2022)
"Cohen studies the role of the Jews in Christian expectations for the end of days, highlighting the complexities of Christian ambivalence regarding the Jews from the Paul's Epistle to the Romans through late antiquity and the across the Middle Ages to early modern Puritanism"--
Keywords: Judaism (Christian theology) / History of doctrines; Christianity and other religions / Judaism; Judaism / Relations / Christianity; End of the world / History of doctrines; Antichrist / History of doctrines; Judaïsme (Théologie chrétienne) / Histoire des doctrines; Christianisme / Relations / Judaïsme; Judaïsme / Relations / Christianisme; Fin du monde / Histoire des doctrines; Antéchrist / Histoire des doctrines; Christianity; Interfaith relations; Judaism